KEJAYAAN INDONESIA SEBAGAI NEGARA MARITIM (JALESVEVA JAYAMAHE) - Yuliati Yuliati (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
A maritime society centered on trade by sea was in Indonesia since pre history. Indonesian anchestor known as sailor who was capable to wadethe ocean until Madagascar, South Africa. Indonesian position in international trade route ancient time which was between India and China influenced on the development of Nusantara maritim history. Sriwijaya, as a kingdom based on maritime as ever dominated maritime trade routes, because its policy, its strategis position and anentreport had showed the glorious Sriwjaya at the time.